2015
DOI: 10.1098/rspb.2015.0389
|View full text |Cite
|
Sign up to set email alerts
|

Sex allocation theory reveals a hidden cost of neonicotinoid exposure in a parasitoid wasp

Abstract: Sex allocation theory has proved to be one the most successful theories in evolutionary ecology. However, its role in more applied aspects of ecology has been limited. Here we show how sex allocation theory helps uncover an otherwise hidden cost of neonicotinoid exposure in the parasitoid wasp Nasonia vitripennis. Female N. vitripennis allocate the sex of their offspring in line with Local Mate Competition (LMC) theory. Neonicotinoids are an economically important class of insecticides, but their deployment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…In our previous research, we demonstrated that exposure to imidacloprid disrupted facultative sex allocation in response to a ‘social’ cue – the presence of co‐foundresses (Whitehorn et al ., ). That initial work showed two important facts about the action of imidacloprid in female N .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In our previous research, we demonstrated that exposure to imidacloprid disrupted facultative sex allocation in response to a ‘social’ cue – the presence of co‐foundresses (Whitehorn et al ., ). That initial work showed two important facts about the action of imidacloprid in female N .…”
Section: Discussionmentioning
confidence: 97%
“…the fertilisation or not of eggs), as single foundress female Nasonia laying eggs alone produced the same sex ratios regardless of imidacloprid dose (see Fig. 2a in Whitehorn et al ., ). This means that imidacloprid does not disrupt the ‘fertilisation‐end’ of sex allocation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations